THE EFFECTIVENESS OF BEETROOT JUICE (BETA VULGARIS) AND IRON TABLETS ON HEMOGLOBIN LEVELS OF PREGNANT WOMEN - Nailul Sakdah; Nurdahliana; Adri Idiana (Department of Midwifery, Health Polytechnic of Aceh, 2022)
Background : The average mortality caused by anemia in Indonesia and Asia is estimated at 7.26%. According to data from the Aceh Besar District Health Office, it is 88 per 100,000 live births. Data on the incidence of anemia at Puskesmas Darul Imarah in December 2018 was 38.8% or 686 women. The main cause of anemia in pregnant women globally is iron deficiency. Iron deficiency occurs as a result of poor diet. One of the efforts made by the Minister of Health of the Republic of Indonesia in the context of preventing and overcoming anemia is by giving 90 tablets of ferrous sulfate tablet. Purposes : This study aimed to determine the effectiveness of beetroot juice (beta vulgaris) and ferrous sulfate tablet (Fe tablet) on hemoglobin levels of pregnant women with mild anemia. Methods : This research was quantitative research with a quasi-experimental design type. This design had a control group, this quasi-experimental research was used to determine the difference between the treated group and the control group. The experimental research design used in this study was in the form of a nonequivalent control group design. The samples of this study were pregnant women with mild anemia in the villages of Gue Gajah and Garot Geuce. Total sample were 30 of pregnant women. Result: There was a significant difference between hemoglobin levels before and after consuming beetroot juice and ferrous sulfate tablets . Conclusion : Consuming 250 ml of beetroot juice together with ferrous sulfate tablet was effective in increasing hemoglobin levels in mild anemic pregnant women.